The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1155/2020/2373021
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Different Dyes’ Potential to Assess Human Normal and Cancer Cell Viability In Vitro under Different D/H Ratios in a Culture Medium

Abstract: In this study, using new approach (laser diffraction + biological dyes), we have demonstrated the decrease of cells viability in vitro in the deuterated growth medium, whereas in the deuterium-depleted medium, there was an increase of cell viability. We have also found that not all dyes are equally sensitive to the D/H ratios in the culture medium (system) as well as to the different cell types (cancer vs normal cells).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The benzotriazolyl esters were tested in terms of cytotoxic activities in A375 human melanoma cells and HaCaT healthy keratinocytes by employing the Alamar Blue cell viability test; cell viability translates into the cells’ ability to perform a specific function or to engage in the mitotic process. The assessment of cell viability is necessary either to establish cell morphological integrity or to monitor cell reactions under various stimuli including toxins or other pharmacologically active compounds [ 22 ]. In the current study, all three semisynthetic compounds exerted a significant dose-dependent cytotoxic effect in melanoma cells when used in concentrations above 25 μΜ; their biological activities exceeded in all cases the ones recorded for the parent compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The benzotriazolyl esters were tested in terms of cytotoxic activities in A375 human melanoma cells and HaCaT healthy keratinocytes by employing the Alamar Blue cell viability test; cell viability translates into the cells’ ability to perform a specific function or to engage in the mitotic process. The assessment of cell viability is necessary either to establish cell morphological integrity or to monitor cell reactions under various stimuli including toxins or other pharmacologically active compounds [ 22 ]. In the current study, all three semisynthetic compounds exerted a significant dose-dependent cytotoxic effect in melanoma cells when used in concentrations above 25 μΜ; their biological activities exceeded in all cases the ones recorded for the parent compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The deuterium concentration in the body plays an important role in the metabolic processes of living systems [ 1 , 2 , 3 , 4 ]. The biological effects caused by deuterium depleted water (DDW) have been studied at various levels: cellular [ 5 , 6 , 7 , 8 ], tissue [ 9 ], organismic [ 10 , 11 , 12 , 13 , 14 ]. It was found that low concentrations of deuterium in the drinking diet increase stress resistance in mammals [ 15 ], and may also have neuroprotective properties [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…No response was observed in the A431 cells based on Trypan blue following treatment with both the WS extract and wsCDs (data not shown).This could be due to the lack of Trypan blue® assay sensitivity in comparison to the Alamar blue™ assay. 42 Due to their absorbance in the UVA (315-400 nm) and UVB (280-315 nm) regions, CDs and their composites have gained importance as UV protectors. 18,[43][44][45][46] In comparison to their parent materials (WS extract), wsCDs showed a 3.6× enhanced…”
Section: Biocompatibility Photo-protection and Antioxidant Activity O...mentioning
confidence: 99%